Lankester-Garten, der Botanische Garten in Cartago, Costa Rica - Morales Sánchez, Carlos (2002)
The Lankester Botanical Garden of the University of Costa Rica was founded in 1973, it was named in honor of the English natural scientist and previous owner Charles H. Lankester (1879-1969). This garden is internationally renowned for its remarkable collection of epiphytes, and is regarded as a centre for preservation of tropical epiphytes, as well as for the research and education work in the fields of conservation and botany. The Lankester Garden owns the largest orchid collection of Central America. In May 2001 the publication of the new botanical journal Lankesteriana was started.